Exploring vestibular dysfunction in primary hypothyroidism using cervical vestibular evoked myogenic potentials - Kars, Ayhan; Atalay, Fatma; Topal, Kübra; Anbar, Sezai Sacid; Akyel, Fatma; Kılıç, Korhan (Cukurova Medical Journal, 2025)
Purpose: This research was conducted to assess cervical vestibular evoked myogenic potential (cVEMP) test responses in patients with primary hypothyroidism without vestibular symptoms. Materials and Methods: Thirty-one patients diagnosed with primary hypothyroidism and who had not yet started on hormone replacement therapy, together with a 26-member control group, were enrolled in the research. All participants underwent detailed otorhinolaryngological examinations and thyroid function, cVEMP, and audiological tests. cVEMP records were compared between the groups. Results: Thirty-one patients aged between 21 and 57 years (38.5±9.7) and a control group of 26 healthy volunteers aged between 20 and 52 years (36.1±8.8) were included in the study. Absent VEMP responses were observed in 12 members of the patient group and in three of the control group. Interpeak amplitudes (IPAs) in both ears were significantly lower in the patient group than in the controls. While no significant difference was found between the groups’ VEMP threshold values, asymmetry rates in both ears were significantly higher in the patient group. Conclusion: cVEMP can be usefully employed in the detection of subclinical